EFFORTS TO IMPROVE THE ABILITY COUNTING STUDENTS OF ELEMENTARY SCHOOL BY UTILIZING NUMBER STICKS: There are many students who have not been able to count and perform arithmetic operations well. This study aims to improve students' numeracy skills by using number sticks. A number stick is a stick-shaped tool that is modified in such a way that there are numbers on it as a tool for counting. This research is a classroom action research with the research subjects of grade 1 students of SDN 024 Muns - Lenni Berty Syamsul (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
There are many students who have not been able to count and perform arithmetic operations well. This study aims to improve students' numeracy skills by using number sticks. A number stick is a stick-shaped tool that is modified in such a way that there are numbers on it as a tool for counting. This research is a classroom action research with the research subjects of grade 1 students of SDN 024 Munsalo Kopah, totaling 15 students with 8 boys and 7 girls. Research implementation in September - October 2019. The instrument used was the observation sheet. The results showed that students' numeracy skills after being given learning using number sticks in the first cycle in the first cycle were 57.22% with a sufficient category. In the second cycle it increased to 64.44% which is in the good category. Based on the results of the study, it can be concluded that the numeracy skills of grade 1 students at SDN 024 Munsalo Kopah have increased with the use of number sticks.